The Tragedy of Existence in Fyodor Dostoevsky’s Notes from the Underground: An Approach to Sartre’s Existentialism - Dian Eka Sari (LINGUA LITERA : journal of english linguistics and literature, 2017)
The tragedy of existence that appears in Fyodor Dostoevsky‘s novel entitled Notes from the Underground is analyzed by applying Jean-Paul Sartre‘s existentialism. The tragedy of man existence is originated from dualism of man freedom. It can be analyzed by applying the concept of absolute freedom which underlies man desire to achieve an ideal existence and the facticities that follow the freedom. Qualitative method that is based on Sartre‘s concept of engagement is applied to describe author‘s involvement as a speaker in literary work. Text is treated as a significant discourse, because words are not merely an object; but the signifiers that consist of meanings, issues, ideas, social situation in specific period. The result of the analysis shows that individual absolute freedom creates possibility to become God toward their own self to conduct acts as well as to recognize the aspects that prohibit them to do so. Man‘s individual freedom tries to surpass the limit, but eventually fails to realize it because of conflict among their consciousness. As the result, man fails to transcend their existence facticities because of other‘s freedom. At the end, it leads to tragedy that forms alienation in inauthentic existence.